2018
DOI: 10.1007/s10803-018-3561-6
|View full text |Cite
|
Sign up to set email alerts
|

Selective Pragmatic Impairment in Autism Spectrum Disorder: Indirect Requests Versus Irony

Abstract: Autism Spectrum Disorder (ASD) is often described as being characterised by a uniform pragmatic impairment. However, recent evidence suggests that some areas of pragmatic functioning are preserved. This study seeks to determine to which extent context-based derivation of non-linguistically encoded meaning is functional in ASD. We compare the performance of 24 adults with ASD, and matched neuro-typical adults in two act-out pragmatic tasks. The first task examines generation of indirect request interpretations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
66
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 80 publications
(99 reference statements)
3
66
0
2
Order By: Relevance
“…Also, social and pragmatic impairments in ASD are rooted in their difficulties to take the other's perspective. 85 We recently showed that sleep loss affects perspective taking in neurotypical adults, 86 a result suggesting that perspective-taking ability is not a mere static trait-like individual feature, but is also partially statedependent. This finding opens a new perspective to better understand the day-to-day variability in ASD social skills, as well as in other neurodevelopmental disorders in which Theory of Mind is challenged, such as, for instance, attention-deficit/hyperactivity disorder.…”
Section: Sleep Impact On Cognition and Sensory Processing: New Insighmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, social and pragmatic impairments in ASD are rooted in their difficulties to take the other's perspective. 85 We recently showed that sleep loss affects perspective taking in neurotypical adults, 86 a result suggesting that perspective-taking ability is not a mere static trait-like individual feature, but is also partially statedependent. This finding opens a new perspective to better understand the day-to-day variability in ASD social skills, as well as in other neurodevelopmental disorders in which Theory of Mind is challenged, such as, for instance, attention-deficit/hyperactivity disorder.…”
Section: Sleep Impact On Cognition and Sensory Processing: New Insighmentioning
confidence: 99%
“…Finally, considering that a lower percentage of SWS and REM sleep predicts diminished social interactions on the following day in neurotypical adults, one may surmise a real‐time effect of sleep on social skills in children with ASD. Also, social and pragmatic impairments in ASD are rooted in their difficulties to take the other's perspective . We recently showed that sleep loss affects perspective taking in neurotypical adults, a result suggesting that perspective‐taking ability is not a mere static trait‐like individual feature, but is also partially state‐dependent.…”
Section: Sleep Impact On Cognition and Sensory Processing: New Insighmentioning
confidence: 99%
“…Of course, one could think of the emergence of language in these children as evidencing a capacity to partially overcome initial social deficits. Yet sociopragmatic impairment constitutes a persistent hallmark of autism, even in individuals whose structural language lies within a typical range (e.g., de Villiers, Fine, Ginsberg, Vaccarella, & Szatmari, 2007;Deliens, Papastamou, Ruytenbeek, Geelhand de Merxem, & Kissine, 2018;Fine, Bartolucci, Szatmari, & Ginsberg, 1994;Kissine, 2012;Surian, Baron-Cohen, & Van der Lely, 1996). It is, therefore, also plausible that language development in ASD may unfold along an alternative acquisition path that does not relate so closely to the communicative function of language.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding how these effects might be modulated by autism, we contrasted two predictions based on previous research in this area. On one hand, if autistic adults experience impairments in processing emotions, inferring the mental states of others, and integrating information in context (as reported in Deliens, Papastamou, Ruytenbeek, Geelhand, & Kissine, 2018;Happé, 1993;Martin & McDonald, 2004), then we would expect delayed or absent integration of characters' emotional states following verbal irony, compared to TD adults. In contrast, if online irony and emotional processing are intact in autistic adults, then we would expect this group to experience the same patterns of integrating emotional states following ironic versus literal criticism as TD adults, and thus Group would not interact with any other variables.…”
Section: Introductionmentioning
confidence: 93%